ASPECTS OF LINGUISTS’ PROFESSIONAL ETHICS IN PROCESSES OF EMANCIPATION AND POLITICAL MANAGEMENT OF LANGUAGE (WESTERN EUROPE > ITALY > SARDINIA): GUIDELINES FOR FURTHER STUDY - Lorinczi, Marinella (European Scientific Journal, ESJ, 2014)
The signs indicating growing worldwide interest in ethics in research are now emerging strongly. In the field of social studies, the communities, associations and institutes of psychology, anthropology and ethnography are those that have taken the lead in proposing and formulating ethical codes, together with the community of linguists, mainly non European. Europe is behind the others not only in the drawing up of a detailed ethical code for linguistic research, but above all in the embodiment and assimilation, of some fundamental ethical principles by operators in the field of European minority and/or endangered languages. The researcher (as the representative of an institution, an agency and so on, that is to say, of cultural elites) is in any case objectively in a position of superiority, prestige and power. Metasociolinguistic practice (including discursive custom) possesses indexicality, as does any other social practice: it is to be desired that all connotations of cultural intraeuropean ‘colonialism’ imposed from above to local counterparts should be avoided. And this can be prevented only by adhering to a formal ethical code accepted by the communities and persons involved. Sardinia (Italy) represents the case study.